2003
DOI: 10.1038/sj.sc.3101489
|View full text |Cite
|
Sign up to set email alerts
|

Effects on age on spinal cord lesion patients' rehabilitation

Abstract: Study design: The present study was undertaken to focus the age-related characteristics of a population of traumatic and nontraumatic spinal cord patients. Objectives: to examine demographic, injury and outcome characteristics of older adults with spinal cord lesions as a result of trauma and nontrauma, and to compare these characteristics with those of younger patients in matched cohorts. Setting: Spinal Cord Unit, Fondazione Santa Lucia IRCCS, a large rehabilitation hospital of the centre-south of Italy. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 24 publications
6
109
1
2
Order By: Relevance
“…Walking function, however, is a very complicated activity, which may be affected by many factors. 12 Motor scores alone do not correlate completely with increased walking function, because other factors such as age, 4 pain, 30,31 balance, 32,33 spasticity, 34 overweight 35 and possibly duration of training may effect walking function. In fact in our patients, motor scores alone show a significant (r ¼ 0.57, Po0.001), but not complete correlation with the WISCI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Walking function, however, is a very complicated activity, which may be affected by many factors. 12 Motor scores alone do not correlate completely with increased walking function, because other factors such as age, 4 pain, 30,31 balance, 32,33 spasticity, 34 overweight 35 and possibly duration of training may effect walking function. In fact in our patients, motor scores alone show a significant (r ¼ 0.57, Po0.001), but not complete correlation with the WISCI.…”
Section: Discussionmentioning
confidence: 98%
“…Walking function, however, is frequently impaired in both groups. 4 Recent epidemiological studies 5 demonstrated that a larger proportion of new traumatic cases presented as incomplete spinal cord lesions (eg some preservation of sensory and/or motor function below the lesion level) and therefore are more likely to regain walking function. Furthermore, advances in emergency medical care and the acute treatment of spinal cord lesions, for example, with methylprednisolone 6,7 suggests efficacy in reducing the severity of neurological impairment, which may also increase the proportion of incomplete lesions with resultant increased probability of recovery of walking function.…”
Section: Introductionmentioning
confidence: 99%
“…12 Neurological recovery was defined on the basis of improvement of motor scores and ASIA impairment grade. 2 Functional status at admission and discharge was assessed by:…”
Section: Methodsmentioning
confidence: 99%
“…Previously, several studies have been published examining the effect of various factors such as age, 2 neurological status at admission 3 and rehabilitation timing 4 on neurological and functional recovery after SCL. However, in spite of the high incidence of non-traumatic lesions, which is considered to vary between 25 and 80% of the total admission for spinal cord injuries, there are still few studies on the influence of different etiologies (namely traumatic vs non-traumatic) on SCL outcome; [5][6][7][8][9][10][11] this is probably due to the different features of the two populations with regard to age, lesion severity and lesion to admission time (LTA), which are wellknown prognostic factors: 5 therefore, the two groups of patients are poorly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…66,67 Thus, it is well recognised that there is substantial improvement in clinical signs in many human patients that suffer incomplete SCI, [68][69][70] which can, indeed, complicate analysis of clinical trials of novel therapeutic interventions. 71,72 However, in common with human SCI patients, there is a subpopulation of affected dogs in which recovery is incomplete or does not occur at all; these affected dogs can be identified with reasonable certainty at an early stage after injury because they lose all sensory and motor function in the hindquarters and pelvic limbs.…”
Section: Treatment and Prognosismentioning
confidence: 99%